Being a vegetarian traveller is not easy. Issue 6 (7th November 2019) - Huang, Yu-Chin; Chen, Li-Hsin; Lu, Cih-Wei; Shen, Jui-Lin
Abstract : Purpose: Previous empirical studies have not documented the link between vegetarians' dietary constraints and travel intentions. Therefore, the purpose of this paper is to utilise a mixed-methods approach to examine the interrelationships of this group's travel motivations, travel constraints, constraint negotiations and behavioural intentions, with special reference to how dietary constraints deter its members from travelling, and its extent. Design/methodology/approach: An online questionnaire was administered to outbound Taiwanese vegetarian travellers ( n =418), and this was followed by in-depth, semi-structured interviews ( n =9) to complement the quantitative data. Findings: The results indicated that vegetarians' dietary constraints significantly deterred them from travelling in certain circumstances: notably, in the company of non-vegetarians. Nevertheless, it was found that some vegetarians efficiently negotiated their constraints and persisted in travelling, in some cases, by compromising their dietary preferences. Practical implications: Travel agents and planners should explore more strategies to meet the needs of vegetarian travellers to increase this group's travel satisfaction. Originality/value: This study established the first theoretical model explaining the relationships among vegetarians' travel motivations, dietary constraints, constraint negotiations and travel intentions.